The Effect of Salience on Chinese Pun Comprehension: A Visual World Paradigm Study - Zheng, Wei; Wang, Yizhen; Wang, Xiaolu (Frontiers in Psychology, 2020)
The present study adopted the printed-word visual world paradigm to investigate the salience effect on Chinese pun comprehension. In such an experiment, participants listen to a spoken sentence while looking at a visual display of four printed words (including a semantic competitor, a phonological competitor, and two unrelated distractors). Previous studies based on alphabetic languages have found robust phonological effects (participants fixated more at phonological competitors than distractors during the unfolding of the spoken target words), while controversy remains regarding the existence of a similar semantic effect. A recent Chinese study reported reliable semantic effects in two experiments using this paradigm, suggesting that Chinese participants could actively map the semantic input from the auditory modality with the semantic information retrieved from printed words. In light of their study, we designed an experiment with two conditions: a replication condition to test the validity of using the printed-word world paradigm in Chinese semantic research, and a pun condition to assess the role played by salience during pun comprehension. Indeed, global analyses have revealed robust semantic effects in both experimental conditions, where participants were found more attracted to the semantic competitors than to the distractors with the emergence of target words. More importantly, the local analyses from the pun condition have shown that the participants were more attracted to the semantic competitors related to the salient meaning of the ambiguous word in a pun than to those related to the less salient meanings within 200 ms after target word offset. This finding suggests that the salient meaning of the ambiguous word in a pun is activated and assessed faster than its less salient counterpart. The initial advantage observed in the present study is consistent with the prediction of the graded salience hypothesis rather than the direct access model.